2021
DOI: 10.3390/sports9090129
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-Limb Strength Asymmetry in Soccer: A Comparison of Professional and Under-18 Players

Abstract: (1) Background: the present study examined the isokinetic peak torque exerted by both knee extensors and flexors, anterior–posterior imbalance and the magnitude and direction of inter-limb asymmetry in professional and academy soccer players. (2) Methods: one hundred soccer players (professional = 50, elite academy = 50) volunteered to take part in this investigation. An isokinetic dynamometer was used to measure the knee extensor (quadriceps) and flexors muscle (hamstrings) torques of the limbs as well as int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 44 publications
(86 reference statements)
2
31
2
Order By: Relevance
“…Regarding SI, peak torque, mean power, and total work of knee flexor muscle in both groups were > 10%, and only in the older group SI peak torque of knee extensor muscle showed the same value. The SI peak torque of knee extensor muscle in the older group found in our study differs from previous studies where values under 10% were found in the elite academy and professional male soccer players (Beato et al, 2021;Bishop, Coratella, et al, 2021). In addition, SI peak torque of knee flexor muscle differs from previous studies where values under 10% were found in professional adult male soccer players (Bishop, Coratella, et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding SI, peak torque, mean power, and total work of knee flexor muscle in both groups were > 10%, and only in the older group SI peak torque of knee extensor muscle showed the same value. The SI peak torque of knee extensor muscle in the older group found in our study differs from previous studies where values under 10% were found in the elite academy and professional male soccer players (Beato et al, 2021;Bishop, Coratella, et al, 2021). In addition, SI peak torque of knee flexor muscle differs from previous studies where values under 10% were found in professional adult male soccer players (Bishop, Coratella, et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…Soccer practices and competitions induce asymmetries. However, these adaptations tend to increase in non-professional players as well as players with intermediate and short training age (Fousekis et al, 2010b;Bishop et al, 2021). Thus, these asymmetries might have influenced the asymmetric results found in the pivot shift maneuver in our study.…”
Section: Discussionmentioning
confidence: 68%
“…When considering absolute reliability however, all CV values were ,10% between test sessions-noting just a slightly elevated value between sessions 1-2 of 10.06%. Given 10% is commonly used as a threshold to determine acceptable levels of absolute reliability during testing (5,6,9,15), it seems that there may have been a very small learning effect across data collection sessions, as CV values improved throughout the weeks. However, practitioners should be mindful that this elevated CV value of 10.06% between sessions 1-2 was only slightly over the accepted 10% threshold, with this value dropping below 10% between sessions 2-3.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of asymmetry was calculated using the formula: (dominant/non-dominant)/total 3 100, as per suggestions by Bishop et al (8) when using bilateral tests, with the dominant limb being defined as the preferred kicking limb for each player. Previous research on this topic has used the Kappa coefficient to determine the direction of asymmetry between test sessions (5)(6)(7)17); however, this statistic is sensitive to large alterations in the outcome if sample sizes are small (35). Thus, levels of agreement for the direction of asymmetry were reported as a percentage of the total sample between each subsequent test session.…”
Section: Statistical Analysesmentioning
confidence: 99%